Study of Nonleptonic Bq∗→DqV and PqD∗ Weak Decays - Qin Chang; Xiaohui Hu; Junfeng Sun; Xiaolin Wang; Yueling Yang (Advances in High Energy Physics)
Motivated by the powerful capability of measurement for the b hadron decays at LHC and SuperKEKB/Belle-II, the nonleptonic B-∗→DD-∗, Dρ-, DK∗-, πD∗, and KD∗ decays are studied. With the amplitudes calculated with factorization approach and the form factors evaluated with the BSW model, branching fractions and polarization fractions are firstly presented. Numerically, the CKM-favored B-q∗→DqDs∗- and Dqρ- decays have branching fractions ~10−8, which should be sought for with priority and firstly observed by LHC and Belle-II. The B-q∗→DqK∗ and Dqρ decays are dominated by the longitudinal polarization states, while the parallel polarization fractions of B-q∗→DqD-∗ decays are comparable with the longitudinal ones; numerically, f∥ + fL≃ 95% and fL:f∥≃5:4. Some comparisons between B-q∗0→DqV and their corresponding B-q0→Dq∗V decays are performed, and the relation fL,∥(B-∗0→DV)≃fL,∥(B-0→D∗V) is found. With the implication of SU(3) flavor symmetry, the ratios Rdu and Rds are discussed and suggested to be verified experimentally.